Policing China : street-level cops in the shadow of protest - Scoggins, Suzanne E., 1979- (Studies of the Weatherhead East Asian Institute, Columbia University., 2021)
"Evaluates the police bureaucracy in modern day China using interview and archival sources. Argues that despite projecting the appearance of a strong security state, the police bureaucracy in China is weak and plagued by problems of resources, enforcement, and oversight in virtually every area of policing except protest response"--